Preparation method of high-performance modified PET film

CN122917360APending Publication Date: 2026-10-16NINGBO INST OF NORTHWESTERN POLYTECHNICAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611050906.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有共混改性方案面临诸多技术挑战:离型剂与PET基体的相容性较差,在熔融共混中难以均匀分散,易发生团聚或析出,导致薄膜表面缺陷;开口剂的粒径和添加量控制不当,虽能起到一定的防粘作用,但往往以牺牲薄膜表面平滑度为代价,难以满足高端应用领域对表面粗糙度的严苛要求

Benefits of technology

通过对功能组分添加顺序、双向拉伸工艺及热处理制度的协同设计,实现了离型性能、力学强度、阻隔性与尺寸稳定性的同步提升,各创新点之间相互促进,产生了单一步骤无法达到的综合效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917360A_ABST
    Figure CN122917360A_ABST
Patent Text Reader

Abstract

The application discloses a kind of preparation methods of high-performance modified PET film: PET raw material is dried to moisture≤0.02wt%;0.1-10% release agent is mixed with dry PET first, then 0.1-3% opening agent is added to obtain premix;PET functional masterbatch is prepared by melt blending, extrusion granulation;After the masterbatch is dried to moisture≤0.02wt%, it is made into non-stretching film by flow casting method;The film is stretched in two directions, and the longitudinal and transverse stretching multiples are both 2-9 times. Wherein, the release agent migrates to the surface of the film and enriches during melt blending and subsequent forming process, forming a low surface energy isolation layer;The opening agent forms a micro-convex structure on the surface of the film, so that the release agent and the opening agent jointly construct a anti-sticking structure with micro-convex and low surface energy cover layer on the surface of the film.The modified PET film prepared by the application has excellent release performance, good mechanical properties and outstanding dimensional thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of modified PET film technology, and in particular to a method for preparing a high-performance modified PET film. Background Technology

[0002] Polyethylene terephthalate (PET) is widely used in the release film industry due to its excellent mechanical properties, thermal stability, and transparency. These release films play an important role in industries such as printing, electronics, and packaging. Most commercially available PET release films use PET film as the base material and apply silicone oil to its surface to impart release properties; therefore, they are often referred to as PET silicone oil films.

[0003] Although the production process of PET silicone film is relatively mature and the release force is controllable, its inherent defects limit its application in high-end fields. On the one hand, the silicone oil coated on the surface of the PET film may migrate to the surface of the substrate material during use, causing contamination to printed circuits, electronic components, etc., affecting the quality of subsequent processing or product performance. On the other hand, the coating process itself affects the thermal history of the PET base film, often leading to a decrease in the dimensional stability of the film and an increase in the thermal shrinkage rate, which in turn adversely affects the performance of the substrate using the PET release film.

[0004] To address the aforementioned shortcomings of coating methods, researchers have attempted to directly add release functional components to the PET matrix through blending modification, aiming to obtain films with intrinsic release properties in a one-step process and avoid the contamination risks and stability issues associated with surface coatings. However, existing blending modification schemes face numerous technical challenges: the release agent has poor compatibility with the PET matrix, making it difficult to disperse uniformly during melt blending, and it is prone to agglomeration or precipitation, leading to surface defects in the film; improper control of the particle size and addition amount of the opening agent, while providing some anti-sticking effect, often comes at the cost of sacrificing the smoothness of the film surface, making it difficult to meet the stringent surface roughness requirements of high-end applications.

[0005] On the other hand, while biaxial stretching is widely used to improve the mechanical properties and dimensional stability of PET films, existing technologies often rely on conventional experience to select the stretch ratio, failing to optimize the design for blends containing functional additives. Conventional stretching processes often fail to effectively solidify the microstructures formed on the surface by additives, leading to unstable release properties. Furthermore, the lack of synergistic matching between the stretch ratio and the additive ratio makes it difficult to simultaneously improve mechanical properties and surface release. For example, if the stretch ratio is too low, the molecular chain orientation is insufficient, resulting in limited improvement in mechanical properties and dimensional stability; if the stretch ratio is too high, it may lead to film breakage or surface structure damage, affecting product yield.

[0006] Therefore, existing technologies still lack a method to prepare PET films with excellent release properties, good mechanical properties, and high dimensional stability through a one-step blending modification process. In particular, there is a technical solution that can synergistically control the additive ratio and stretching process parameters to comprehensively improve the overall performance of the film while curing the anti-stick structure on the surface, so as to meet the stringent requirements of high-end application fields such as release films for the overall performance of the film. Summary of the Invention

[0007] To address the aforementioned shortcomings, this invention proposes a method for preparing a high-performance modified PET film, which yields a high-performance modified PET film that combines excellent release properties, good mechanical properties, and outstanding dimensional thermal stability.

[0008] This invention provides the following technical solution: a method for preparing a high-performance modified PET film, comprising the following steps: S1. Dry the PET raw material to control its moisture content to ≤0.02wt%; S2. First, mix 0.1-10% of the release agent (by weight of PET raw material) with the dried PET raw material, and then mix 0.1-3% of the opening agent (by weight of PET raw material) with the aforementioned mixture to obtain a premix. S3. The premixed material is melt-blended, extruded and granulated to obtain PET functional masterbatch; S4. Dry the PET functional masterbatch to control its moisture content ≤0.02wt%; S5. The dried PET functional masterbatch is made into an unstretched film by casting. S6. The unstretched film is biaxially stretched, wherein the stretching ratio in both the longitudinal and transverse directions is 2-9 times independently, to obtain a high-performance modified PET film. In this process, the release agent migrates to and accumulates on the film surface during melt blending and subsequent molding, forming a low surface energy isolation layer; the opening agent forms a microscopic protrusion structure on the film surface, so that the release agent and the opening agent together construct a composite anti-stick structure with microscopic protrusions and a low surface energy covering layer on the film surface.

[0009] As an improvement, the drying process in steps S1 and S4 is carried out at 80℃-170℃ to control the moisture content to ≤0.02wt%.

[0010] As an improvement, the drying processes in steps S1 and S4 are carried out under vacuum or inert atmosphere to effectively prevent PET from oxidizing or thermally degrading during high-humidity drying.

[0011] As an improvement, in step S3, melt blending is performed using a twin-screw extruder at a processing temperature of 250℃-290℃ to ensure that the release agent and opening agent are fully and uniformly dispersed in the PET matrix.

[0012] As an improvement, the casting method includes the step of casting the melt onto the surface of a cooling roller at a surface temperature of 10°C-50°C to facilitate the initial fixation of the synergistic anti-sticking structure formed by the release agent and the opening agent on the film surface.

[0013] As an improvement, step S6, after biaxial stretching, also includes a heat setting step at 180°C-240°C to eliminate internal stress, stabilize the crystalline structure, and improve the dimensional thermal stability of the modified PET film.

[0014] As an improvement, the release agent is a compound containing long-chain alkyl groups and polar functional groups selected from ester, amide, or carboxyl groups. The release agent is selected from at least one of rice bran wax, amide-modified polyethylene wax, glyceryl monostearate, and sodium salt of ethylene-acrylic acid copolymer, so that it can migrate to and accumulate on the film surface during melt blending and subsequent molding processes.

[0015] As an improvement, the opening agent is an inorganic or organic rigid particle with an average particle size in the range of 2μm to 5μm. The opening agent is selected from at least one of silica, diatomaceous earth, talc, mica flakes, dicalcium phosphate, nano-TiO2 coated SiO2, and organosilicon microspheres, so that the opening agent and the release agent jointly construct a composite anti-sticking structure with microscopic protrusions and a low surface energy coating layer on the film surface.

[0016] As an improvement, in step S2, the amount of release agent added is 4wt%-6wt% of the PET raw material mass, and the amount of opening agent added is 1.5wt%-2.5wt% of the PET raw material mass.

[0017] As an improvement, the surface of the prepared modified PET film has a micro-protrusion structure with a peak height of 0.1-1.0 μm formed by the opening agent, and the surface is covered with a low surface energy layer formed by the release agent; the average surface roughness Ra of the modified PET film is 1.0-1.5 μm.

[0018] Compared with the prior art, the advantages of the present invention are as follows: By synergistically designing the order of functional component addition, biaxial stretching process, and heat treatment regime, simultaneous improvements in release properties, mechanical strength, barrier properties, and dimensional stability were achieved. The various innovations mutually reinforced each other, producing a comprehensive effect that could not be achieved by a single step. First, a stepwise mixing method, adding the release agent first and then the opening agent, ensures uniform dispersion of the two functional components in the PET matrix, avoiding the agglomeration and competitive adsorption problems common in traditional blending. This uniformly dispersed microstructure provides an ideal precursor structure for the free migration of the release agent and the orderly protrusion of the opening agent. During melt blending and casting, the release agent molecules continuously migrate and accumulate to the film surface, forming a low surface energy isolation layer, reducing the surface tension to 20-30 mN / m. Simultaneously, the opening agent particles with a diameter of 2-5 μm are frozen on the surface, forming island-like peaks 0.1-1 μm higher than the surface, with accompanying annular pits forming a concave-convex structure. The migrated release agent is seamlessly coated on these microscopic undulations, forming a composite anti-sticking structure of chemically low surface energy + physical microscopic isolation, drastically reducing the actual contact area to below 10% and the peel force to 14-20 g, approximately 70% lower than that of pure PET film. Here, the low surface energy of the release agent not only provides a release effect itself, but also amplifies the anti-sticking effect of physical isolation by reducing the adhesion of the peak surface; while the presence of the peak protects the release agent layer from direct frictional wear, and the two work together to extend the release life.

[0019] Furthermore, the biaxial stretching step becomes a key step in solidifying and reinforcing this synergistic structure. Under stretching of 2-9 times in both the longitudinal and transverse directions, and a total area ratio of 4-81 times, the PET molecular chains undergo high orientation, inducing the formation of a fine and uniform crystalline structure, increasing crystallinity to 35-45%, and tensile strength to over 120 MPa. This orientation and crystallization process produces two important synergistic effects: First, flow-induced crystallization anchors the already formed concave-convex release structure in situ, solidifying it on the film surface, making the peak morphology and release agent layer less prone to deformation or detachment during subsequent high-temperature processing or repeated use, ensuring the long-lasting stability of the release effect. Second, the high orientation and densification of the chain segments significantly reduces the diffusion coefficient of small molecules, lowering oxygen permeability to 5-10 cm⁻¹. 3 / (m 2 The release agent (0.1 MPa) not only improves the barrier properties but also slows down the backflow of the release agent into the matrix, thus synergistically enhancing the release and barrier properties.

[0020] The 80℃-240℃ heat setting step, combined with biaxial stretching, further synergizes with the process: while eliminating tensile stress, it stabilizes the crystalline structure and the aforementioned surface anti-stick morphology, ensuring that the film exhibits no wrinkling after hot pressing at 190℃ for 3 minutes, and that the heat shrinkage rate is controlled to within 1.0% after 30 minutes at 150℃. This excellent dimensional thermal stability ensures that in high-temperature bonding scenarios, the surface micro-protrusions and low surface energy layer will not collapse or fail to cover due to film shrinkage, thus guaranteeing reliable release under extreme conditions.

[0021] Furthermore, precise control of drying temperature (80℃-170℃) and atmosphere (vacuum or inert atmosphere) effectively suppresses the hydrolysis and thermal degradation of PET, ensuring the intrinsic strength of the matrix and providing a material basis for high-strength films. Melt blending temperature (250℃-290℃) ensures sufficient dispersion of functional components, providing a prerequisite for subsequent migration and the construction of uniform protrusions. Cooling roller surface temperature (10℃-50℃) rapidly fixes the initial distribution of the aforementioned functional components on the surface, providing a structural template for biaxial stretching. This precise coordination of process parameters enables synergistic operation across the entire chain, from matrix protection to structural construction and performance curing, ultimately resulting in a high-performance modified PET film with low peel strength, high strength and toughness, high barrier properties, and high dimensional stability. Attached Figure Description

[0022] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments: Figure 1 This is a schematic diagram of the biaxial stretching process of an unstretched diaphragm, in which... Figure 1 (a) in the diagram is a schematic diagram of the diaphragm without biaxial stretching. Figure 1 (b) is a schematic diagram of the diaphragm after biaxial stretching; Figure 2 These are scanning electron microscope (SEM) images comparing the surface morphology of the high-performance modified PET film prepared in this embodiment of the invention with that of the comparative pure PET film. Figure 2 (a) in the figure shows the surface morphology of the pure PET film in the comparative example, which shows a smooth and flat surface structure; Figure 2 (b) in the figure shows the surface morphology of the modified PET film prepared in the embodiment of the present invention; Figure 3 These are three-dimensional microscopic morphology comparison images of the high-performance modified PET film prepared in this embodiment and the comparative pure PET film, wherein... Figure 3 Image (a) shows that the surface of the pure PET film is a nanoscale smooth mirror finish. Figure 3 Image (b) shows that the surface of the modified PET film of the present invention has a uniformly distributed protrusion structure; Figure 4 This is a comparison of the total reflectance infrared (ATR) spectra of the high-performance modified PET film prepared in the embodiments of the present invention and the pure PET film. Detailed Implementation

[0023] Example 1 like Figures 1 to 4 As shown, a method for preparing a high-performance modified PET film includes the following steps: S1. Dry the PET particles in an oven at 120℃. After drying, test the moisture content of the particles with a halogen moisture meter to ensure that the moisture content of the dried PET particles is ≤0.02wt%. The dried PET particles are then ready for use. S2. First, mix the release agent rice bran wax with the dried PET raw material, then mix the opening agent silica (1 wt%) with the above mixture to obtain a premix. S3. The premixed material is melt-blended, extruded and granulated to obtain PET functional masterbatch; S4. Dry the PET functional masterbatch in an oven at 120℃. After drying, test the moisture content of the particles with a halogen moisture analyzer to ensure that the moisture content of the dried PET functional masterbatch is ≤0.02wt%, and obtain the dried PET functional masterbatch. S5. The dried PET functional masterbatch is made into an unstretched film by casting. S6. The unstretched film is biaxially stretched simultaneously, with the longitudinal stretching ratio being 3 times and the transverse stretching ratio being 3 times, to obtain a high-performance modified PET film.

[0024] In step S2, the mass fractions of rice bran wax were 0.1 wt%, 5 wt%, and 10 wt%, respectively.

[0025] The prepared high-performance modified PET film was cut into 10cm×10cm square samples, covered on a stainless steel plate, and hot-pressed at 190℃ and 0.5MPa pressure for 3 minutes. After cooling to room temperature, its peel strength was tested using an electronic tensile testing machine at a peel speed of 300mm / min and a peel angle of 180°. The test results are shown in Table 1.

[0026] Table 1. Peel strength test results of modified PET films with different rice bran wax contents. As shown in Table 1, the PET release film with 0.1 wt% rice bran wax exhibited the highest peel force (60 g) after hot pressing with a stainless steel plate. This indicates that a small amount of rice bran wax cannot form an effective wax crystal isolation layer between the PET film and the stainless steel plate, thus failing to achieve a good release effect. The PET release film with 5 wt% rice bran wax showed the lowest peel force (14 g), indicating the best release effect. The PET release film with 10 wt% rice bran wax was brittle and easily broken during peeling after hot pressing with the stainless steel plate, and its peel force was 36 g, which was greater than the 14 g peel force when 5 wt% was added. This suggests that excessive release agent leads to a decrease in the mechanical properties of the PET film. Furthermore, excessive wax melts and is extruded under high temperature and pressure, migrating to the PET-steel plate interface to form an oil phase layer. The thick oil layer has a low thermal conductivity, resulting in insufficient cooling of the PET, low crystallinity, and reduced shrinkage stress, making it even more difficult to release.

[0027] Example 2 In step S2, the mass fraction of rice bran wax is 5 wt%, and the mass fractions of silica are 0.1 wt%, 2 wt%, and 3 wt%, respectively.

[0028] The remaining steps and parameters are the same as in Example 1, so they will not be repeated here.

[0029] The prepared high-performance modified PET film was cut into 10cm × 10cm square samples, and peel strength tests were performed according to the method described in Example 1. The test results are shown in Table 2.

[0030] Table 2. Peel strength test results of modified PET films with different silica contents. Table 2 shows that the peel force is 46g when 0.1wt% silica is added, indicating that a small amount of opening agent cannot form a sufficiently dense raised structure on the film surface, and the effect of reducing the contact area is limited. The peel force is the lowest at 20g when 2wt% silica is added, showing the best release effect. The PET release film with 3wt% silica has the highest peel force of 50g after hot pressing with a stainless steel plate, indicating that excessive silica is not easily dispersed evenly in PET, cannot form uniform bumps to reduce the contact area, and will also affect the film-forming properties of PET, which is actually detrimental to demolding.

[0031] Example 3 In step S2, the rice bran wax has a mass fraction of 5 wt%, and the silica has a mass fraction of 2 wt%. In step S6, the unstretched diaphragm is biaxially stretched, wherein the stretching ratios are as follows: The longitudinal stretch ratio is 2 times, and the transverse stretch ratio is 2 times; The longitudinal stretch ratio is 5 times, and the transverse stretch ratio is 5 times; The longitudinal stretch ratio is 9 times, and the transverse stretch ratio is 9 times; The longitudinal stretch ratio is 3 times, and the transverse stretch ratio is 6 times; The longitudinal stretch ratio is 6 times, and the transverse stretch ratio is 3 times; The stretching speed was 60 mm / s, the stretching temperature was 105℃, and after stretching, the material was heat-set at 200℃ for 30 seconds. All other steps and parameters were the same as in Example 1.

[0032] The prepared high-performance modified PET film was cut into 10cm×10cm pieces, covered on a stainless steel plate, and hot-pressed at 190℃ for 3 minutes. After cooling to room temperature, the film was visually inspected to see if wrinkles appeared. The test results are shown in Table 3.

[0033] Table 3. Wrinkle state of modified PET films after high-temperature hot pressing at different biaxial stretching ratios As shown in Table 3, when the longitudinal and transverse stretching ratios of the biaxially stretched film are both independently within the range of 2-9 times, and the total area stretching ratio is within the range of 4-81 times, the high-performance modified PET films prepared do not exhibit wrinkling after hot pressing at 190℃ for 3 minutes, proving that different stretching ratio combinations can ensure good dimensional thermal stability. Asymmetric stretching (such as 3×6 and 6×3) can adjust the differences in mechanical properties of the film in the longitudinal and transverse directions according to application requirements.

[0034] Example 4 This embodiment is used to compare and analyze the differences in surface morphology and release properties between the modified PET film and the pure PET film of the present invention.

[0035] The modified PET film of this invention was prepared according to the formulation and process described in Example 1, which contained 5 wt% rice bran wax and 1 wt% silica. As a comparison, a pure PET film was prepared using the same process but without the addition of rice bran wax and silica.

[0036] The surface morphology of the thin film was observed using a Hitachi SU8010 field emission scanning electron microscope at an accelerating voltage of 5 kV and a magnification of 5000x. (Reference) Figure 2 (b) SEM images of the modified PET film of this invention show that silica opening agent particles with a particle size of 2-5 μm are uniformly frozen on the film surface, forming island-like peak structures 0.1-1 μm above the surface. The particles are surrounded by annular pits of 1-3 μm, and the peaks and pits together constitute a bump-concave structure. This microstructure verifies that the opening agent selected in this invention can form an effective micro-protrusion structure on the film surface, providing a structural basis for achieving physical isolation and anti-sticking.

[0037] The three-dimensional morphology of the thin film surface was analyzed using a three-dimensional microscope, with a scanning range of 10 μm × 10 μm. (Reference) Figure 3 (a) A microscopic image of the surface morphology of the pure PET film shows that its surface is a nanoscale smooth mirror surface, and its average surface roughness Ra value is measured to be 0.578 μm. (Refer to...) Figure 3 (b) The three-dimensional microscopic morphology image of the modified PET film of the present invention shows that the film surface has a uniformly distributed protrusion structure, with an average surface roughness Ra value of 1.174 μm and the height of the protrusion peaks mostly distributed in the range of 0.1-1.0 μm. The above comparative results show that the microscopic protrusions formed by the opening agent can reduce the actual contact area between the film and the substrate from nearly 100% to less than 10%, thereby significantly reducing the negative pressure effect and van der Waals force, and achieving excellent anti-sticking and release properties.

[0038] Total reflectance infrared (ATR) spectroscopy analysis of the thin film surface was performed using a Nicoletti S50 Fourier transform infrared spectrometer, with a scanning range of 4000-400 cm⁻¹. -1 The resolution is 4cm. -1 The number of scans was 32. (Refer to...) Figure 4 The ATR infrared spectrum of the modified PET film of this invention is at 2920 cm⁻¹. -1 and 2850cm -1 A distinct absorption peak for the CH stretching vibration appears nearby, at 1730 cm⁻¹. -1 The presence of C=O stretching vibration absorption peaks nearby, corresponding to the characteristic absorptions of long-chain alkyl and ester groups in rice bran wax, indicates that the release agent has migrated to the film surface to form a low surface energy coating layer. However, these characteristic peaks were not observed in the ATR infrared spectrum of pure PET film.

[0039] Based on the above surface morphology analysis and infrared spectroscopy analysis results, it is proven that the present invention successfully constructs a composite anti-stick structure with microscopic protrusions and a low surface energy coating layer on the film surface through the synergistic effect of release agent and opening agent, realizing a dual release effect of chemical low surface energy and physical microscopic isolation, thereby significantly improving the release performance of the film.

[0040] It is understood that the release agent is not limited to rice bran wax, but may also be a compound containing long-chain alkyl groups and polar functional groups, such as amide-modified polyethylene wax, glyceryl monostearate, and sodium salt ionomer of ethylene-acrylic acid copolymer.

[0041] Obviously, the opening agent is not limited to silicon dioxide, but can also be inorganic or organic rigid particles with an average particle size in the range of 2μm to 5μm, such as diatomaceous earth, talc, mica sheets, dicalcium phosphate, nano-TiO2 coated SiO2, and organosilicon microspheres.

[0042] It is understood that the drying temperature is not limited to 120°C, but can be selected in the range of 80°C-170°C, and can be carried out under vacuum or inert atmosphere to effectively prevent PET from oxidizing or thermally degrading during high-temperature drying.

[0043] Obviously, the processing temperature of the melt blending is not limited to 260°C, but can also be selected in the range of 250°C-290°C to ensure that the release agent and the opening agent are fully and uniformly dispersed in the PET matrix.

[0044] It is understood that the surface temperature of the cooling roller in the casting process is not limited to 30°C, but can be selected in the range of 10°C-50°C, so as to facilitate the initial fixation of the synergistic anti-sticking structure formed by the release agent and the opening agent on the film surface.

[0045] Obviously, the heat setting temperature is not limited to 200℃, but can also be selected in the range of 180℃-240℃ to eliminate internal stress, stabilize the crystalline structure and improve the dimensional thermal stability of the modified PET film.

[0046] The above description only illustrates the preferred embodiments of the present invention and should not be construed as limiting the scope of the claims. The present invention is not limited to the above embodiments, and variations in its specific structure are permitted. All modifications made within the scope of the independent claims of this invention are also within the scope of protection of this invention.

Claims

1. A method for preparing a high-performance modified PET film, characterized in that, Includes the following steps: S1. Dry the PET raw material to control its moisture content to ≤0.02wt%; S2. First, mix 0.1-10% of the release agent (by weight of PET raw material) with the dried PET raw material to obtain a mixture. Then, mix 0.1-3% of the opening agent (by weight of PET raw material) with the aforementioned mixture to obtain a premix. S3. The premixed material is melt-blended and extruded to granulate to obtain PET functional masterbatch; S4. The PET functional masterbatch is dried to control its moisture content to ≤0.02wt%; S5. The dried PET functional masterbatch is made into an unstretched film by casting. S6. The unstretched diaphragm is subjected to bidirectional stretching, wherein the stretching ratio in both the longitudinal and transverse directions is 2-9 times independently, the stretching temperature is 80-120℃, and the stretching speed is 10-100mm / s. The release agent migrates and accumulates on the film surface during melt blending and subsequent molding, forming a low surface energy isolation layer; the opening agent forms a microscopic protrusion structure on the film surface, so that the release agent and the opening agent together construct a composite anti-stick structure with microscopic protrusions and a low surface energy covering layer on the film surface.

2. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, The drying processes described in steps S1 and S4 are both carried out at 80℃-170℃ to control the moisture content to ≤0.02wt%. The drying temperature is monitored and controlled in real time by a temperature sensor.

3. The method for preparing a high-performance modified PET film according to claim 2, characterized in that, The drying processes described in steps S1 and S4 are carried out under vacuum or inert atmosphere to effectively prevent PET from oxidizing or thermally degrading during high-humidity drying.

4. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, In step S3, the release agent and opening agent are melt-blended using a twin-screw extruder at a processing temperature of 250℃-290℃ to ensure that they are fully and uniformly dispersed in the PET matrix.

5. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, The casting method includes the step of casting the melt onto the surface of a cooling roller with a surface temperature of 10℃-50℃ to form a film, so as to initially fix the synergistic anti-sticking structure formed by the release agent and the opening agent on the film surface.

6. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, Step S6, after the biaxial stretching, also includes a heat setting step at 180°C-240°C to eliminate internal stress, stabilize the crystalline structure, and improve the dimensional thermal stability of the modified PET film.

7. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, The release agent is a compound containing long-chain alkyl groups and polar functional groups selected from ester groups, amide groups or carboxyl groups. The release agent is selected from at least one of rice bran wax, amide-modified polyethylene wax, glyceryl monostearate, and sodium salt of ethylene-acrylic acid copolymer, so that it can migrate to and accumulate on the film surface during melt blending and subsequent molding.

8. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, The opening agent is an inorganic or organic rigid particle with an average particle size in the range of 2μm to 5μm. The opening agent is selected from at least one of silica, diatomaceous earth, talc, mica flakes, dicalcium phosphate, nano-TiO2 coated SiO2, and organosilicon microspheres, so that the opening agent and the release agent jointly construct a composite anti-sticking structure with microscopic protrusions and a low surface energy coating layer on the film surface.

9. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, In step S2, the amount of release agent added is 4wt%-6wt% of the mass of PET raw material, and the amount of opening agent added is 1.5wt%-2.5wt% of the mass of PET raw material.

10. The method for preparing a high-performance modified PET film according to claim 1, characterized in that, The surface of the prepared modified PET film has a microscopic protrusion structure with a peak height of 0.1-1.0 μm formed by the opening agent, and the surface is covered with a low surface energy layer formed by the release agent; the average surface roughness Ra of the modified PET film is 1.0-1.5 μm.